Effect of microgravity on spatial orientation and posture regulation during coriolis stimulation - Takahashi, Masahiro; Sekine, Motoki; Ikeda, Takuo; Watanuki, Koichi; Hakuta, Shuzo; Takeoka, Hajime (Acta Oto-Laryngologica, 2004)
Objective To elucidate spatial orientation and posture regulation under conditions of microgravity. Material and Methods Coriolis stimulation was done with five normal subjects on the ground (1g) and onboard an aircraft (under conditions of microgravity during parabolic flight). Subjects were asked to tilt their heads forward during rotation at speeds of 0, 50, 100 and 150°/s on the ground and 100°/s during flight. Body sway was recorded using a 3D linear accelerometer and eye movements using an infrared charge-coupled device video camera. Flight experiments were performed on 5 consecutive days, and 11-16 parabolic maneuvers were done during each flight. Two subjects boarded each flight and were examined alternately at least five times. Results Coriolis stimulation at 1g caused body sway, nystagmus and a movement sensation in accordance with inertial inputs at 1g. Neither body sway, excepting a minute sway due to the Coriolis force, nor a movement sensation occurred in microgravity, but nystagmus was recorded. Conclusions Posture, eye movement and sensation at 1g are controlled with reference to spatial coordinates that represent the external world in the brain. Normal spatial coordinates are not relevant in microgravity because there is no Z-axis, and the posture regulation and sensation that depend on them collapse. The discrepancy in responses between posture and eye movement under conditions of microgravity may be caused by a different constitution of the effectors which adjust posture and gaze.